Integrated hybrid ventilative cooling technology for residential buildings in tropical savannah climate - Eso, Olamide (2025)
The tropical savannah climate, particularly in Sub-Saharan Africa, is characterised by daytime temperatures as high as 35–37°C and generally low wind speeds of 2–4 m/s. This complicates indoor thermal comfort without mechanical cooling. As a result, energy demand for residential air conditioning and ventilation increases. Meanwhile, residential air conditioning contributes significantly to greenhouse gas emissions. The study presents the design, validation, and performance analysis of an Encapsulated Phase Change Material Hybrid solar fan assisted Multi-directional Windcatcher system. The study aimed to assess effective cooling, and temperature stabilisation performance without compromising on acceptable ventilation in residential buildings within tropical savannah climates, specifically in Sub-Saharan Africa. The novelty of this research lies in the vertical integration of encapsulated PCM tubes within the windcatcher’s airstreams. The system also combines with hybrid ventilation through fan-assisted airflow during low wind speeds. The fan provides an additional 370L/s airflow. This ensured consistent ventilation and addressed the limitations of passive windcatcher systems, such as inconsistent airflow. The optimal passive cooling material selected for this study was the RT28HC paraffin PCM, with a melting point of 27–29°C. It was chosen for its efficiency in regulating indoor temperatures without the energy-related costs of air conditioning systems. Encapsulating the PCM in tubes (EPCM-T) ensured consistent heat transfer, which improved the thermal storage capability. The study employed Computational Fluid Dynamics (CFD) simulations to evaluate the system’s performance under different climatic conditions. Simulations explored various EPCM tube configurations and their effects on airflow, cooling, and thermal storage efficiency. The findings have indicated that the EPCM-HMW system can reduce supply air temperature by up to 3.15°C (9% temperature reduction) compared to conventional windcatcher systems without PCM. Supply air dropped to 305 K (31.85 oC) in the best-case scenario. This occurred when outdoor air temperature was as high as 308 K (35 oC). This temperature drop was essential for maintaining indoor comfort without mechanical cooling, particularly during peak heat when outdoor air is or exceeds 308 K (35 oC). The study findings also showed that the air supply offered by the system achieved temperature stabilisation for approximately 5 hours. However, cooling (indoor temperature reduction) continued for 7 hours. The ventilation performance, although lower than that of a conventional windcatcher, was still within acceptable thermal comfort limits of 140.86 L/s air flow rate, sufficient for 14 to 17 occupants. The EPCM-HMW system consumed 95% less energy than a ductless split AC unit, equating to 20 times lower energy consumption. Annual energy savings were estimated at $2,707.2 (£2,152), with net savings over 20 years amounting to $23,690.71 (£19,070.81). The system achieved a payback period of approximately 8.24 years and an ROI of 106.2%. This research demonstrates the significant long-term financial benefits of adopting the EPCM-HMW system. It also advances windcatcher technology by integrating thermal energy storage to enhance cooling efficiency and temperature stabilisation. The outcomes of this research would be beneficial to broader applications of PCM-based hybrid cooling systems in tropical savannah climates. The study offers a practical, low-energy solution for residential ventilative cooling in high-temperature and low wind regions with limited energy infrastructure. The research also suggests future work in optimising PCM encapsulation techniques and conducting further field testing to further validate the system’s real-world performance.